“We are not the same”: African women’s view of multipurpose prevention products in the TRIO clinical study - Shapley-Quinn MK; Manenzhe KN; Agot K; Minnis AM; van der Straten A (Dove Medical Press, 2019)
Mary Kate Shapley-Quinn,1 Kgahlisho N Manenzhe,2 Kawango Agot,3 Alexandra M Minnis,1,4 Ariane van der Straten1,5 On behalf of the TRIO study team 1Women’s Global Health Imperative (WGHI) RTI International, San Francisco, CA, USA; 2Setshaba Research Centre, Soshanguve, South Africa; 3Impact Research and Development Organization, Kisumu, Kenya; 4School of Public Health, UC Berkeley, Berkeley, CA, USA; 5Department of Medicine, Center for AIDS Prevention Studies, UCSF, San Francisco, CA, USA Purpose: Unintended pregnancy and HIV infection present dual risks for young women in sub-Saharan Africa. New multipurpose prevention technologies (MPTs) are in development to simultaneously prevent unintended pregnancy and HIV, but there is a need for end-user research to ensure these products suit women’s needs. The Tablet, Rings and Injectables as Options (TRIO) for women study took place in Kisumu, Kenya, and Soshanguve, South Africa, with the goal of eliciting young women’s feedback on three potential MPTs. Methods: Women in TRIO used three placebo products that represented potential MPTs: daily oral tablets, monthly vaginal rings, and monthly dual injections in a randomized crossover design followed by a period in which they chose a product to use. Eighty-eight TRIO participants completed in-depth interviews and focus group discussions to understand their experiences using each product. Qualitative analyses were conducted after stratifying by product preference at the end of the crossover period. Results: The majority (65%) of participants preferred injections, with the remainder evenly split between tablets and rings. Discussions of preference for one product were closely linked with expressed dislike of another product’s attributes. Participants recognized heterogeneity in preferences and choices across users and stressed the need for multiple MPT options that confer a low burden on women’s daily lives. Conclusion: Rather than choosing a product to use based on the product’s perceived advantages, women’s choices were based on the unfavorable attributes of other TRIO products. Moreover, the importance that women placed on a given disadvantage varied. Disadvantages that women deemed as most important emerged as a greater driver of product preference than selecting products based on their advantages and favorable characteristics. Keywords: end-user research, HIV prevention, contraception, product preference, qualitative research